Bibliometrics versus altmetrics: Researchers’ attitudes in Slovakia - Melicherová, Michaela; Ondrišová, Miriam; Šušol, Jaroslav (Iberoamerican Journal of Science Measurement and Communication, 2021)
Objective. The paper presents principal theoretical starting points and an overview of attitudes to altmetrics-based research evaluation among scientists of various disciplines in Slovakia, more specifically in comparison with traditional, bibliometric approaches. Design/Methodology/Approach. We used a questionnaire and asked researchers from various disciplines about their knowledge of principle characteristics defining the altmetrics and about their attitudes towards the application of bibliometrics and altmetrics approaches in the processes of research evaluation. The questionnaire covered a wide range of issues, predominantly associated with interpretation and perception of the importance of alternative indicators, including the factors influencing the interpretation. In this analysis, we concentrate on those parts of research reflecting the willingness of respondents to accept alternative indicators as part of research/science assessment. Results/Discussion. The attitude to the application of alternative indicators in research assessment is not significantly more negative among Slovak scientists if we compare it to other countries. The citations are still a respected indicator perceived as a tool for creating bonds within science. If they are perceived as obsolete or insufficient, it relates to the experience of researchers whose results are predominantly aimed at non-academic target group or if they are active in the research of social phenomena and problems. Due to pragmatic reasons connected with research financing, however, registering the citations is a generally accepted priority. Familiarity and practical experience with social media were identified as one of the factors influencing the interpretation of alternative indicators in the environment of both public and academic media. Conclusions. Traditional bibliometric methods, especially in the area of research evaluation, are still preferred over the altmetrics. The scientists realize that the kind of attention captured by the indicators based on social media is not comparable with the citation-based impact. Or, more precisely, that altmetrics reflects a different kind of impact whose correspondence with a traditional world of bibliographic citations remains to be explored. Originality/Value. The article presents the results of original research carried out in the community of scientists in Slovakia, applying quantitative research methods. It contributes to the results of previous studies on the attitudes and acceptance of altmetrics in the research community, with a special focus on research assessment.